Examination of the psychological process that a goalkeeper gets over failure. How does soccer goalkeeper get over the loss of a goal. - Fukui, K.; Toyoda, N. (Japanese Journal of Sport Psychology, 2015)
In recent years, the high specificity and specialty of the goalkeeper (GK) in soccer have attracted interest. However, the psychological aspects of the GK remain unclear. Therefore, the purpose of this study was to clarify the process by which the GK gets over from the loss of a goal. Using a semi-structured interview, 4 male college student GKs were interviewed about shocking goal losses and how they get over from them. Results were analyzed using the Modified Grounded Theory Approach (M-GTA); 7 categories containing 20 concepts were generated. The following hypothetical idea was developed: "When experiencing a goal loss, the GK will face various contradictions stemming from an unrealistic GK image. The GK will build a GK style of his own that is realistic and adaptive, due to accept a goal loss while then adapt to contradictions". This hypothetical idea contained counterfactual thinking, self-regulated learning, and adaptation, and suggested the possibility that the goal-loss experience led to increased maturity in the GK. Therefore, it was suggested that GK coach could constitute a training methods including rebound mentality.